Pathotype Identification of Rice Blast Pathogen, Pyricularia oryzae Using Differential Varieties in Peninsular Malaysia - Siti Norsuha Misman; Latiffah Zakaria (Tropical Life Sciences Research, 2019)
Seven pathotypes of Pyricularia oryzae were differentiated from blast disease samples collected from 2014–2016, using eight Malaysian differential rice varieties. Pathotype P7.0 is the dominant pathotype identified (33.9%) followed by P0.0, P1.0 and P9.0 which are currently become more abundant in the field with frequency of 20.0% for P0.0, and 15.4% for both P1.0 and P9. Pathotype P7.0 was mostly isolated from MR220CL2, MR263 and MR219 rice varieties which are popular variety planted by farmers in Peninsular Malaysia. Interestingly, new emergence of pathotype P0.2 has been identified, which was isolated from a new released variety, MR284 as well as blast isogenic line IRBL 20 carrying Pi5(t) blast resistance gene. Prolong planting of more than 20 planting seasons and large scale planting of MR219 and MR220 with current varietal coverage areas of more than 90% in Peninsular Malaysia are suspected as possible reason for P7.0 become dominant. Varietal coverage of MR220CL2 and MR263 has reached about 50% might be the cause of changes in blast pathogen pathotype dominancy to P0.0, P1.0 and P9.0. Tujuh patotip Pyricularia oryzae telah dibezakan daripada sampel-sampel penyakit karah yang diperolehi dari 2014–2016 menggunakan lapan varieti padi pembeza Malaysia. Patotip P7.0 adalah patotip dominan yang dikenal pasti (33.9%) diikuti dengan P0.0, P1.0 dan P9.0 di mana ketika ini patotip-patotip ini didapati meningkat di lapangan dengan frekuensi 20.0% bagi P.00, dan 15.4% bagi kedua-dua P1.0 dan P9. Patotip P7.0 kebanyakannya dipencil daripada MR220CL2, MR263 dan MR219 yang merupakan varieti popular ditanam oleh petani di Semenanjung Malaysia. Menariknya, kemunculan patotip baru, P0.2 telah dikenalpasti dan dipencilkan daripada varieti baru yang diperkenalkan, MR284 dan titisan isogenik IRBL 20 yang membawa gen rintang karah Pi5 (t). Tempoh penanaman melebihi 20 musim dan penanaman MR219 dan MR220 dalam skala besar dengan kawasan liputan lebih daripada 90% di Semenanjung Malaysia berkemungkinan menyebabkan patotip P7.0 menjadi dominan. Dengan peningkatan kawasan liputan penanaman varieti MR220CL2 dan MR263 menghampiri 50% ketika ini disyaki menyebabkan perubahan pada kedominan patotip patogen karah kepada P0.0, P1.0 dan P9.0.